2023
DOI: 10.1038/s41477-023-01445-6
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of seagrass communities in a changing climate

Abstract: Although climate change projections indicate significant threats to terrestrial biodiversity, the effects are much more profound and striking in the marine environment. Here we explore how different facets of locally distinctive α- and β-diversity (changes in spatial composition) of seagrasses will respond to future climate change scenarios across the globe and compare their coverage with the existing network of marine protected areas. By using species distribution modelling and a dated phylogeny, we predict w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…This study highlighted the strong effect of latitude on the probability of seagrass presence (Short et al, 2007), with seagrass being more likely to occur at latitudes >18° S (Carter et al, 2021). The negative relationship between longitude and alpha diversity indices observed in our results suggests a potential role for longitudinal variation in shaping seagrass diversity (Daru et al, 2023).…”
Section: Alpha Diversity Relationship With Constrain Variablessupporting
confidence: 52%
See 1 more Smart Citation
“…This study highlighted the strong effect of latitude on the probability of seagrass presence (Short et al, 2007), with seagrass being more likely to occur at latitudes >18° S (Carter et al, 2021). The negative relationship between longitude and alpha diversity indices observed in our results suggests a potential role for longitudinal variation in shaping seagrass diversity (Daru et al, 2023).…”
Section: Alpha Diversity Relationship With Constrain Variablessupporting
confidence: 52%
“…On the other hand, the lack of significant influence of environmental drivers on seagrass alpha diversity indices (Carter et al, 2021), apart from dominant substrate type (Nordlund et al, 2017), contrasts with the findings of previous studies (Nordlund et al, 2017). The Great Barrier Reef study identified various environmental conditions (Carter et al, 2021), including depth (Short et al, 2007), water temperature (Shields et al, 2019;Marbà et al, 2022 andDaru et al, 2023), and salinity (Bell et al, 2019;Misson et al, 2021), which are important factors in predicting seagrass presence and influencing the extent of seagrass communities. Similarly, a study on seagrass-associated fauna emphasized the influence of physical structure and environmental factors such as nutrient enrichment (Heck et al, 2000;Qin et al, 2021), exposure to waves and tides, and large-scale disturbances (Hirst et al, 2017;Uhrin and Turner, 2018).…”
Section: Alpha Diversity Relationship With Constrain Variablesmentioning
confidence: 83%
“…In this sense, expected larger thermal instability towards higher latitudes is minored and so the principle of the rule is difficult to be tested. The mid-domain effect does not seem here to play any effect, because some seagrass species with wide ranges have their latitudinal midpoints at high latitudes, and seagrasses are not found at polar latitudes where they potentially could expand (Daru & Rock, 2023).…”
Section: Discussionmentioning
confidence: 92%
“…A total of 32 temperate and 29 tropical species were here considered according to Rolland et al (2014) criteria (−23.4° and 23.4° as the threshold latitudes defining the tropics). Although these are broad-scale approximations of seagrass distributions, they provide a reliable approximation to model distributions of seagrasses (Daru & Rock, 2023); because the IUCN periodically updates these distribution maps, this is the most accurate source of seagrass distribution (Daru et al, 2017).…”
Section: Data Sourcementioning
confidence: 99%
See 1 more Smart Citation